A Nexus Model of Restricted Interests in Autism Spectrum Disorder - Carter, R. McKell; Jung, Heejung; Reaven, Judy; Blakeley-Smith, Audrey; Dichter, Gabriel S. (Frontiers in Human Neuroscience, 2020)
Restricted interests in autism spectrum disorder are clinically impairing interests of unusual focus or intensity. They are a subtype of restricted and repetitive behaviors which are one of two diagnostic criteria for the disorder. Despite the near ubiquity of restricted interests in autism spectrum disorder, the neural basis for their development is not well understood. However, recent cognitive neuroscience findings from nonclinical samples and from individuals with autism spectrum disorder shed light on neural mechanisms that may explain the emergence of restricted interests. We propose the nexus model of restricted interests in autism spectrum disorder, a novel conceptualization of this symptom domain that suggests that restricted interests may reflect a co-opting of brain systems that typically serve to integrate complex attention, memory, semantic, and social communication functions during development. The nexus model of restricted interests hypothesizes that when social communicative development is compromised, brain functions typically located within the lateral surface of cortex may expand into social processing brain systems and alter cortical representations of various cognitive functions during development. These changes, in turn, promote the development of restricted interests as an alternative process mediated by these brain networks. The nexus model of restricted interests makes testable predictions about reciprocal relations between the impaired development of social communication and the emergence of restricted interests in autism spectrum disorders and suggests novel avenues for treatment development.